PENGARUH RELIGIUSITAS, FINANCIAL LITERACY, RISK PERCEPTION DAN RISK TOLERANCE TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI PADA CASH WAQF LINKED DEPOSIT - Wirdiansah, Muhamad; Syarifudin, Efi; Peristiwo , Hadi (AkMen JURNAL ILMIAH, 2025)
Investment in Islamic financial instruments, such as cash waqf linked deposit (CWLD), is the latest innovation of social investment issued by the Indonesian Waqf Agency, but investment decisions in this product are influenced by various factors, such as individual religiosity, financial literacy, risk perception, and risk tolerance. These factors are known to play an important role in investment decisions, but there have been no studies that test its influence on investment decision-making in CWLD. This study aims to analyze the influence of religiosity, financial literacy, risk perception, and risk tolerance on investment decision-making in cash waqf linked deposit (CWLD) products. A quantitative approach was used in this study with a survey method through a questionnaire distributed to 150 respondents of a sample of banking employees at two different banks. Data analysis was carried out using the Partial Least Square method to test the influence of each independent variable partially and simultaneously on the dependent variable. The results of the study show that religiosity, financial literacy, risk perception, and risk tolerance have a significant and simultaneous influence on investment decision-making in Cash Waqf Linked Deposit (CWLD). Religiosity and risk perception have a strong positive influence on investment decision-making. Meanwhile, financial literacy and risk tolerance have a more limited influence on investment decision-making. In conclusion, religiosity, financial literacy, risk perception, and risk tolerance have a positive and simultaneous influence on investment decision-making in Cash Waqf Linked Deposit (CWLD).